The dynamic interplay of capability strengths and weaknesses: investigating the bases of temporary competitive advantage - Sirmon, David G.; Hitt, Michael A.; Arregle, Jean‐Luc; Campbell, Joanna Tochman (Strategic Management Journal, 2010)
Abstract Foundational RBV work suggests that firms possess capabilities that represent strengths and others that represent weaknesses. In contrast, contemporary research has examined capability strengths while largely ignoring weaknesses. Addressing this oversight, we examine the direct and integrated effects of sets of capability strengths and capability weaknesses on competitive advantage and its empirical correlate—relative performance. Additionally, we explore how environmental and firm‐specific factors influence change in these drivers of competitive advantage over time. Results suggest that weakness sets have a negative effect on relative performance, while strength sets have an increasingly positive effect. The integrative effects of strength and weakness sets affect relative performance in a complex manner. For example, while high strength/low weakness firms perform at high levels, firms integrating high strength with high weakness perform well, but experience considerably more variance in their realized outcomes. Lastly, we find that the strength and weakness sets change significantly over time in markets where competition is more intense, thereby undermining the durability of competitive advantage. Our theory and results indicate that achieving temporary advantage is more difficult than previously thought and that the erosion of advantage occurs routinely as a result of dynamic and interactive rivalry. Copyright © 2010 John Wiley & Sons, Ltd.